Digital Literacy Seminar: "Caring for Personal Data Security in the Digital World" - Anton Yudhana; Rusydi Umar; M. Rosyidi Djou; Maulana Muhammad Jogo Samodro; Awaludin Makku (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Technology is becoming a tool to improve human performance, especially in the era of the Industrial Revolution 4.0, which is currently developing rapidly. The connectedness of various systems through the internet has led Indonesia to have 212.9 million internet users, covering 77% of the total population, with 78.5% of them active on social media. This phenomenon has brought about unprecedented growth in collecting and storing personal data that should be watched out for. Protecting personal data is essential, especially as internet users grow, increasing individuals' vulnerability to cybercrime. From 2022 to 2023, scams via WhatsApp messages manipulated with malicious attachments of images or links have become prevalent. To overcome this challenge, MTI UAD, in collaboration with the Regional Leadership of 'Aisyiyah Alor Regency, organized a digital literacy seminar to increase mothers' knowledge about the importance of protecting personal data in the digital world to minimize the risk of fraud. As a result, after attending the seminar, participants' knowledge increased significantly from under 50% to around 73%. Personal data protection efforts include sharing information, avoiding receiving files or applications from unknown sources, social engineering, and installing applications only from trusted sources.